Evaluation of Bio-Mos® Mannan Oligosaccharide as a Replacement For Growth Promoting Antibiotics in Diets for Turkeys - Fritts, C.A.; Waldroup, P.W. (International Journal of Poultry Science, 2002)
A study was conducted to evaluate the use of Bio-Mos®, a mannan oligosaccharide derived from the cell wall of yeast, as a potential replacement for growth promoting antibiotics in the diet of growing turkeys. Bio-Mos® was added to nutritionally complete turkey diets at the rate of 0.05 and 0.10%. The growth-promoting antibiotics bambermycins and bacitracin methylene disalicylate (BMD) were added at 2.2 and 55 mg/kg, respectively. One group was fed the diet with no supplements and served as the negative control. Male turkeys of a commercial Large White strain were fed the test diets from day old to 20 wk of age. Birds were weighed at intervals through the trial and samples of birds processed at 20 wk for parts yield and determination of intestinal breaking strength. Body weight, mortality, breast meat yield, and intestinal breaking strength were not significantly (P < 0.05) influenced by dietary treatments. Feed conversion from 0 to 20 wk of age was significantly improved by both BMD and 0.10% Bio-Mos®. The addition of BMD significantly reduced the percentage of abdominal fat in the carcass. These results suggest that Bio-Mos® might be considered as a part of an overall feeding and management program to aid in overcoming potential loss of growth-promoting antibiotics.